Introducing the Wonders of Nature: A Collaboration of Religion and Science for Early Childhood - Sujani, Elfara Hajjar (Proceeding International Conference on Religion, Science and Education, 2025)
This research explores how introducing the wonders of nature through the collaboration of religion and science can enhance early childhood education. Utilizing a qualitative approach and library research, it investigates theories related to child development, religious education, and science instruction for young children. The focus is on how integrating religion and science can promote environmental awareness and spiritual values from an early age. The results indicate that religious education and science teaching complement one another. Religious values such as gratitude, responsibility, and respect for nature provide a strong moral foundation, while science education helps children develop a rational understanding of natural phenomena, like the water cycle and photosynthesis. This combined approach not only fosters intellectual growth but also encourages the development of children's environmental consciousness and character. The study also highlights the crucial role that parents and teachers play in holistically merging religious and scientific teachings. A comprehensive curriculum tailored to children's developmental stages is essential for effectively introducing the wonders of nature. This form of education aims to impart both academic knowledge and a sense of responsibility for environmental stewardship. In conclusion, the collaboration between religion and science offers an effective educational model for early childhood, nurturing a generation that is both intellectually and spiritually aware. This is vital for fostering environmental sustainability and equipping children to meet future challenges.